Pemodelan Jaringan Komputer Berbasis LAN dan WLAN di Perusahaan Ekspedisi Menggunakan Metodologi PPDIOO - Zone Tryando Gemenio Brahmana; Handrie Noprisson (JSAI (Journal Scientific and Applied Informatics), 2025)
Network models are the primary infrastructure supporting smooth operations, ranging from managing shipment data to inter-branch communication and real-time package tracking. With an optimally designed network, companies can maintain stable connections between devices and systems, accelerate information processing, and enhance responsiveness to customer needs. This study aims to develop and optimize the LAN (Local Area Network) and WLAN (Wireless Local Area Network) at PT APZ using the PPDIOO (Prepare, Plan, Design, Implement, Operate, Optimize) method adapted from Cisco’s approach. Considering the limitations in adding network devices, the study designs an efficient and reliable network using hardware such as the ASUS RT-AC68U router, Procurve Switch 1800-24g, Engenius EAP300 wireless devices, and Vascolink UTP (Unshielded Twisted Pair) CAT 6 cables. Network simulation and design were conducted using Cisco Packet Tracer version 8.2.2 on a system powered by an Intel Core i3-6006U processor with 8 GB of RAM (Random Access Memory) and Windows 10 Pro 64-bit operating system. Test results showed a significant improvement in network performance, with a download speed of 33.82 Mbps, upload speed of 33.38 Mbps, and a low ping response time of 7 ms, indicating a stable network operation.